Is Abusive Supervision the Last Straw? The Buffering Role of Construal Level in the Association of Abusive Supervision With Withdrawal - Gao, Riguang; Liu, Bo (Frontiers in Psychology, 2022)
Drawing on the theory of cognitive-affective processing system and that of construal level, we propose a moderated mediation model illustrating the relationship among abusive supervision, shame, construal level, and work withdrawal. We tested this model with a two-source time-lagged survey of 387 employees from 129 work teams in central and East China. Results revealed that abusive supervision has a positive association with the emotion of shame and supported the mediating role of shame linking abusive supervision to work withdrawal. Besides, our findings supported the buffering effect of construal level on the shame-work withdrawal relationship as well as the indirect relationship between abusive supervision and work withdrawal channeled through the emotion of shame.